Prospective Teachers’ Self-Regulation: The History of Mathematics as a Tool for Perseverance - Rita Panaoura (Education Sciences)
The present study investigated the effect of improving prospective teachers’ self-regulation to teach mathematics at primary education through the mathematical courses they attended at a pedagogical department. Forty-eight students of a pedagogical department participated in the conducted quantitative study. The implemented intervention program, which consisted of two math content courses and a teaching methodology course on mathematics, emphasized the acquaintance of unsolved mathematical problems, the historical development of mathematical concepts, the obstacles faced during the development of concepts through the centuries, and the process of mathematical continuity and development. The use of the history of mathematics aimed to enhance participants’ self-regulatory abilities about the learning and teaching of mathematics. We had used data from tools administered four times over a period of the four years of their studies: at the beginning of their studies, after two math content courses, after a course about the teaching of mathematics, and after the field work at a school. The analysis of those data showed that there was an improvement in their mathematical performance and their self-regulation ability to solve problems, but there was a decrease in their self-efficacy beliefs to teach mathematics and to self-regulate their respective teaching behavior. We discuss the effectiveness of the program on the specific dimension and the implications of the design of teacher education programs grounded in the history of mathematics, with the aim to enhance prospective teachers’ self-regulation on handling difficult situation during the teaching of mathematics.